2006
DOI: 10.1016/j.otohns.2005.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Radial Forearm Free Flap Donor Site Outcomes Comparison by Closure Methods

Abstract: Each of the 3 methods of reconstruction has low morbidity and satisfactory aesthetic and functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 24 publications
(47 reference statements)
4
65
0
1
Order By: Relevance
“…Most of the complaints are about poor appearance (2%Y8%), delayed wound healing with partial failure of the skin graft (2%Y53%), exposure of tendons (0%Y33%), contracture of scars (11%), sensory impairment of the donor hand (17%Y54%), and cold intolerance (27%). 12,13 To overcome these complications, alternative ways of restoring the radial forearm free flap donor site other than split thickness skin graft have been explored; these include full thickness skin grafts, 14 acellular dermal matrix (Alloderm), 14 and negative pressure wound dressings. The Alloderm, composite graft of acellular dermal matrix and ultrathin split thickness skin graft, produced greater patient satisfaction and functional recovery of the forearm.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the complaints are about poor appearance (2%Y8%), delayed wound healing with partial failure of the skin graft (2%Y53%), exposure of tendons (0%Y33%), contracture of scars (11%), sensory impairment of the donor hand (17%Y54%), and cold intolerance (27%). 12,13 To overcome these complications, alternative ways of restoring the radial forearm free flap donor site other than split thickness skin graft have been explored; these include full thickness skin grafts, 14 acellular dermal matrix (Alloderm), 14 and negative pressure wound dressings. The Alloderm, composite graft of acellular dermal matrix and ultrathin split thickness skin graft, produced greater patient satisfaction and functional recovery of the forearm.…”
Section: Discussionmentioning
confidence: 99%
“…In a comparative study of RFF donor site closure methods, Ho et al [4] studied three techniques for donor site repair, STSG, STSG with AlloDerm and FTSG. They found that the group of patients reconstructed with STSG alone achieved the highest esthetic outcome ratings .…”
Section: Discussionmentioning
confidence: 99%
“…Techniques such as direct closure, prelamination or full thickness skin graft (FTSG) instead of split thickness skin graft (STSG) at RFF donor defect have been employed, but STSG is still the method of choice for many surgeons [2][3][4][5], including those at our institute, Seoul National University Dental Hospital.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical advantage of the improved cosmetic appearance is appealing, but a recent study in the head and neck cancer literature showed no statistical difference in aesthetic or functional outcomes when comparing donor sites closed with split thickness grafts, full thickness grafts and Alloderm plus split thickness grafts. It was a small study, but the perceived benefit of using the dermal substitute may be more theoretical than real [10].…”
Section: Additional Usesmentioning
confidence: 99%